The Moderating Effect of Goodwill and Goodwill Impairment on Global Energy Crisis and Corporate Cash Holding - Ghiga Rachmawati Saleh (JASF: Journal of Accounting and Strategic Finance, 2022)
The global energy crisis caused a price spike in various operational inputs for the companies; sufficient cash is required to ensure the company's operations continue. This study aims to analyze the causal effect of the energy crisis on corporate cash holdings in Indonesia and the role of goodwill and impairment of goodwill in moderating this effect. Goodwill and goodwill impairment are indicators of corporate risk related to the synergy of business combinations. This study uses the differences in differences method. There are 564 companies listed on the Indonesia Stock Exchange, including those in the sample of this study, with a quarterly research period from the 4th quarter of 2020 until the 2nd quarter of 2022. The hypotheses were tested using the linear regression analysis and robustness test. This study found that the global energy crisis has a positive effect on corporate cash holdings for the impacted sub-industry. However, goodwill and goodwill impairment are not moderate influences. This study also discusses its limitations. For further research, it is expected to add more control variables, use another robustness test, and increase the observation period until the global energy crisis is over.